Firms' resilience to financial constraints: The role of trade credit - Isaac Marcelin; Daniel Brink; Wei Sun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We study the role of trade credit in enhancing the resilience of financially constrained firms from 2010 to 2017. Implicit borrowing in trade finance allows financially constrained firms to bridge the financing gap, expand employment by 8.26 per cent, and increase average firm profits significantly. Trade finance suppliers, not financially constrained firms, experience a surge of 7.99 per cent in the average rate of sales growth. Corporate resilience to financial constraints occasioned by trade credit is quite robust to controlling for relevant factors and employing various estimation techniques. While countries strive to develop their financial sector to fund economic activity and growth, they need to facilitate a business environment that promotes trade credit flows among firms as a second-best alternative to bank financing.
Keywords: E24; G32; L25; O5; 330; financial constraints; trade credit; employment; firm profits; sales growth